1st Annual Conference of Midwifery - Yulizawati (De Gruyter, 2020)
Indonesian Midwifery Research, that primarily focuses on midwives, midwifery practices and education, is trying to make a tremendous effort to reveal the consequences of industrial development which influences midwifery practice and midwifery educational. The 1st Annual Conference of Midwifery has proven its commitment to promote the spirit of the scientist which provides insight, innovation, and creativity to resolve the problems in the midwifery field which occurred in this industrial development era. Hundreds of scientists, professionals, and students have gathered to discuss, analyse, and express their opinions about the current issues today. We are proud because we can bridge their efforts in a prestigious scientific gathering in Indonesia at The 1st ACM 2019. Aims &amp Scope This event will bring together midwifery experts, midwifery researcher, midwifery lecturer, and students worldwide. We expect it to be a great opportunity and an inspiring occasion for research development learning, especially to the disseminating of new findings in midwifery and to bridge the networking of midwifery professional, midwifery researcher and midwifery educator. Scopes: • Pregnancy • Childbirth • Postpartum • New born care • Women's health • Reproductive health • Techniques of teaching and learning • Literacy and skill development • Digital technology on education • Creativity and entrepreneurship education • Innovation and value on education • Health Profession Education. • Educational Theory • Early Childhood Education • Parenting in the era of industrial revolution 4.0 Instructions for Authors https://drive.google.com/file/d/1N2uWrHr-EaH_5K6ol-kpHHpLCvsuM67